2018
DOI: 10.1097/md.0000000000009553
|View full text |Cite
|
Sign up to set email alerts
|

Dentist's distress in the management of chronic pain control

Abstract: We aimed to obtain greater understanding of dentists’ distress when they diagnose and treat patients with temporomandibular disorders (TMD), and to explore ways in which TMD can be better treated.We conducted a cross-sectional study based on a questionnaire survey of dentists (n = 148). Dentists were queried using an open-ended questionnaire about distress they experienced when treating patients with TMD. Survey responses were analyzed using mixed methods. Associations between specific dentist and patient char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Simmons discussed the insufficient training of dentists in diagnosing temporomandibular disorders [16]. Similarly, dentists' distress in diagnosing and managing TMD pain was shown in a study by Yokoyama et al [17]. Other studies reported similar conclusions, not only with the lack of standardized physical evaluation [18] but also with the lack of psychological assessment [19].…”
Section: Discussionmentioning
confidence: 84%
“…Simmons discussed the insufficient training of dentists in diagnosing temporomandibular disorders [16]. Similarly, dentists' distress in diagnosing and managing TMD pain was shown in a study by Yokoyama et al [17]. Other studies reported similar conclusions, not only with the lack of standardized physical evaluation [18] but also with the lack of psychological assessment [19].…”
Section: Discussionmentioning
confidence: 84%
“…This translates to a “hidden” cost to employers of £584 and £1,225 in lost productivity for each 6-month period among individuals living with TMD ( 9 , 10 ). The natural history and etiology of the disorder are poorly understood and thus, appropriate treatment options are difficult to determine, limited, and complex ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have reported that treating TMD can reduce HAs [ 6 33 42 43 44 45 46 ]. However, many dentists are uncomfortable diagnosing or treating TMD [ 47 48 49 ]; one study of recent dental graduates attributed their lack of confidence in TMD diagnosis and treatment to insufficient TMD training in the dental school curricula [ 48 ]. TMD management generally focuses on conservative reversible therapy, including counseling, physical therapy, pharmacotherapy, behavior modification following self-care instructions, and intraoral occlusal appliances [ 19 ].…”
Section: Introductionmentioning
confidence: 99%